Trust no one - Heggan, Christiane (St. Martin's Press, 1999)
Over the past two decades, Nick Horrigan has built a quiet, safe life for himself, living as much under the radar as possible. But all of that shatters when, in the middle of the night, a SWAT team bursts into his apartment, grabs him and drags him to a waiting helicopter. A terrorist--someone Nick has never heard of--has seized control of a nuclear reactor, threatening to blow it up. And the only person he'll talk to is Nick, promising to tell Nick the truth behind the events that shattered his life twenty years ago.